Dormancy release and chilling requirement of buds of latitudinal ecotypes of Betula pendula and B. pubescens - Myking, T.; Heide, O. M. (Tree Physiology, 1995)
Bud burst and dormancy release of latitudinal ecotypes of Betula pendula Roth and B. pubescens Ehrh. from Denmark (≈ 56° N), mid-Norway (≈ 64° N) and northern Norway (≈ 69° N) were studied in controlled environments. Dormant seedlings were chilled at 0, 5 or 10 °C from October 4 onward and then, at monthly intervals from mid-November to February, batches of seedlings were held at 15 °C in an 8-h (SD) or 24-h (LD) photoperiod to permit flushing. A decline in days to bud burst occurred with increasing chilling time in all ecotypes. In November, after 44 chilling days, time to bud burst was least in plants chilled at 0 and 5 °C. The difference diminished with increasing chilling time, and in February, after 136 chilling days, bud burst was earliest in plants chilled at 10 °C. Long photoperiods during flushing significantly reduced thermal time after short chilling periods (44 and 74 days), but had no effect when the chilling requirement was fully met after 105 or more chilling days. No significant difference in these responses was found between the two species. In both species, chilling requirement decreased significantly with increasing latitude of origin. Bud burst was normal in seedlings overwintered at 12 °C, but was erratic and delayed in seedlings overwintered at 15 and especially at 21 °C, indicating that the critical overwintering temperature is between 12 and 15 °C. We conclude that there is little risk of a chilling deficit in birch under Scandinavian winter conditions even with a climatic warming of 7–8 °C. The likely effects of a climatic warming include earlier bud burst, a longer growing season and increased risk of spring frost injury, especially in high latitude ecotypes.